ROOTS TO THE WINGS: THE APOSTOLIC CHRIST-EXPERIENCE AND ITS ORGANIC GROWTH IN THE SYRO-MALABAR QURBANA - Kalambukattu, Naiju Jose (Asian Horizons, 2017)
The Church as a community is founded on and rooted in Christ witnessed by the apostles (Eph 2:20). As a result, their witness underpins the life and Tradition of the Church and the primary and paramount mission of the Church is to protect and preserve the deposit of the apostolic faith perfect and intact (1 Tim 6:20). The apostolic roots of the faith are kept unbroken in the Holy Qurbana and in it a faithful can trace the roots of his or her faith. Hence, the apostolic roots and patristic orientations are to be protected and preserved in the liturgy and an organic continuity is to be maintained to have abundant fruits of faith.